CLUBHOUSE AS VIRTUAL COMMUNITY OF PRACTICE FOR NON-NATIVE ENGLISH SPEAKERS TO PRACTICE - Zahra, Fatimah Az; Yappi, Shierly N. (Academy of Education Journal, 2023)
Clubhouse application, since it is found, becomes the popular application to practice English. It is because it is easy to use worldwide as well as provides good features and a community system. This case study investigated whether the Clubhouse application could become a virtual community of practice (VCoP) and motivate non-native English speakers (NNES) to speak within the community system. The data were collected through questionnaires with a Likert scale and semi-structured interviews. The participants were the members of the Smart and Easy English club, one of the biggest English clubs in the Clubhouse, who come from Morocco, Afghanistan, and Indonesia. The results revealed some points including 1) Based on the club system, Clubhouse can become an ideal IDLE for VCoP; 2) Clubhouse application motivates the NNES to practice English in the VCoP depending on the features and system used by the club or community; 3) The leadership role in the club does not influence the NNES to practice on Clubhouse as VCoP. The study concluded that Clubhouse is a virtual community of practice which features and community system motivate non-native English speakers to practice English regularly. The findings suggested that the Clubhouse application can be used by English instructors to enable their learners to have English-speaking practice in VCoP. The results of this study may be advantageous for English-speaking course developers with contemporary channel practice.